Microsoft Word 2010 plain & simple - Murray, Katherine, 1961- (Sebastopol, Calif. : O'Reilly, 2010)
Presents step-by-step instructions on the essentials of the word processing program, covering such topics as creating different types of documents, formatting, editing, reviewing, publishing documents on the Web, and integrating with other Office products.
1. About this book : No computerspeak! ; A quick overview ; What's new in Word 2010 ; A few assumptions ; A final word (or two) -- 2. Getting started with Word 2010 : Creating a new document ; Starting with a template ; Working with an existing document ; Introducing backstage view ; Adding content ; Adding hyperlinks ; Printing a document ; Getting help -- 3. Editing your content : Editing basics ; Changing your view ; Navigating through the document ; Converting old documents ; Reading a document ; Moving and copying text ; Replacing text ; Inserting building blocks ; Correcting your spelling and grammar ; Correcting text automatically ; Researching a subject ; Translating your text -- 4. Formatting documents : Choosing and changing themes ; Applying and saving styles ; Changing style sets ; Formatting text ; Creating a bulleted or numbered list ; Customizing a bulleted or numbered list ; Creating a multilevel list ; Customizing a multilevel list ; Changing character font and size ; Adjusting paragraph line spacing ; Adjusting the spacing between characters ; Setting paragraph alignment ; Indenting a paragraph -- Formatting with tabs ; Adding text boxes ; Creating a dropped capital letter ; Copying your formatting ; Placing a line border around a page ; Placing an art border around a page ; Adding a decorative horizontal line ; Adding a border or shading to a paragraph -- 5. Designing great layouts : Customizing a template ; Designing a template ; Laying out the page ; Changing page orientation ; Changing margins in a document ; Fine-tuning your layout ; Creating sections ; Adding columns ; Creating a table from scratch ; Using a predesigned table ; Creating a table from text ; Adding or deleting rows and columns in a table ; Positioning elements in a table ; Customizing a table layout ; Aligning a table ; Moving a table ; Formatting a table ; Creating a table style -- 6. Adding graphics to your documents : Inserting a picture ; Changing the size of a picture ; Adding Clip Art ; Adding shapes ; Editing and formatting a picture ; Getting artistic with pictures ; Removing picture backgrounds ; Wrapping text around a graphic ; Arranging multiple graphics ; Positioning graphics on the page ; Creating artistic text ; Inserting a rational diagram ; Creating a chart -- 7. Word 2010 for blogging, mailing, and more : Creating an online document ; Including a file within a file ; Writing and publishing a blog ; Printing an envelope ; Printing a mailing label ; Creating a form letter ; Personalizing a form letter -- 8. Adding special features for long documents : Creating headers and footers ; Creating variable headers and footers ; Organizing your information ; Reorganizing a document ; Creating a master document ; Inserting a cover page ; Creating footnotes and endnotes ; Creating a table of contents ; Creating an index -- 9. Sharing, co-authoring, and finalizing your document : Using the Word 2010 web app ; Co-authoring a document ; Contacting co-authors ; Reviewing shared file information ; Working with revision marks ; Comparing changes in a document ; Combining reviews ; Viewing documents side by side ; Finalizing your document -- 10. Customizing and securing Word : Customizing the ribbon ; Customizing the Quick Access Toolbar ; Customizing the work area ; Changing the location and type of saved files ; Customizing your spelling dictionaries ; Creating a macro ; Changing file validation ; Choosing what's displayed in protected view ; Password protecting a file ; Limiting file changes ; Recovering unsaved versions.
Includes index.
Keywords: Microsoft Word; Word processing; Microsoft Word (Computer software); Word processing software